Core-, pan- and accessory genome analyses of Clostridium neonatale: insights into genetic diversity (2022)
ABSTRACT: Clostridium neonatale is a potential opportunistic pathogen recovered from faecal samples in cases of necrotizing enterocolitis (NEC), a gastrointestinal disease affecting preterm neonates. Although the C. neonatale species description and name validation were published in 2018, comparative genomics are lacking. In the present study, we provide the closed genome assembly of the C. neonatale ATCC BAA-265T (=250.09) reference strain with a manually curated functional annotation of the coding sequences. Pan-, core- and accessory genome analyses were performed using the complete 250.09 genome (4.7Mb), three new assemblies (4.6–5.6Mb), and five publicly available draft genome assemblies (4.6–4.7Mb). The C. neonatale pan-genome contains 6840 genes, while the core-genome has 3387 genes. Pan-genome analysis revealed an ‘open’ state and genomic diversity. The strain-specific gene families ranged from five to 742 genes. Multiple mobile genetic elements were predicted, including a total of 201 genomic islands, 13 insertion sequence families, one CRISPR-Cas type I-B system and 15 predicted intact prophage signatures. Primary virulence classes including offensive, defensive, regulation of virulence-associated genes and non-specific virulence factors were identified. The presence of a tet(W/N/W) gene encoding a tetracycline resistance ribosomal protection protein and a 23S rRNA methyltransferase ermQ gene were identified in two different strains. Together, our results revealed a genetic diversity and plasticity of C. neonatale genomes and provide a comprehensive view of this species genomic features, paving the way for the characterization of its biological capabilities.